ANALISIS YURIDIS EFEKTIVITAS PT. PEGADAIAN TANJUNG BALAI KARIMUN DALAM MELAKUKAN PENIMBANGAN BARANG BUKTI NARKOTIKA DIKAITKAN DENGAN TUJUAN HUKUM ACARA PIDANA - Muhammad Alkasah; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Narcotics crime is a criminal offense known in Law Number 35 of 2009 concerningNarcotics. Strategic policies need to be carried out by the government so that trade inprohibited goods and users of prohibited goods such as narcotics and the like can beprevented, so that the enormous negative impact on the creation of the Unitary State ofIndonesia can be overcome. Therefore, however, every perpetrator of drug abuse must besubject to 1 severe punishment so that the perpetrator is deterred or does not repeat the act ofselling and using the prohibited item. The formulation of the problem in this study is how thelegal regulation for the implementation of weighing narcotics evidence (methamphetamine)submitted by the Tanjung Balai Karimun Police Department to PT. Pegadaian is associatedwith evidence in Tanjung Balai Karimun PN and how effective the weighing of evidencecarried out by the ditresobat to PT. Tanjung Balai Karimun pawnshop is associated withcriminal procedural law.The method in this study uses empirical juridical legal research methods. This researchis also referred to as literature research or document study. It can also be called field research.In this study, it was used to collect and find data and information through field studies at theKarimun Regional Police on the basic assumptions used in answering a problem in this study.The results of this study, the first result was obtained that, in the Legal Regulation forthe Implementation of Weighing Narcotics Evidence (shabu) submitted by the Tanjung BalaiKarimun Police Department to PT. This pawnshop cannot be applied optimally because theprocedure in weighing narcotics evidence has not been explained in writing about theprocedure or why weighing must be at PT. The pawnshop. This has an effect on supportingthe judge's performance in giving decisions so that judges have clear guidelines in imposingsanctions, the severity of criminal sanctions imposed. Second, that the effectiveness ofweighing evidence carried out by Ditresobat to PT. Tanjung Balai karimun pawnshop can besaid to have not run fully effectively. So it can be concluded that it is necessary to change thebasis to regulate more competent irregularities to be able to carry out the weighing ofevidence, especially in this serious drug crime.Keywords: Evidence, Narcotics, Code of Criminal Procedure.